(untitled) (Journal of Engineering, 2013)
In this paper, three tool paths strategies; iso-planar, helical and adaptive have been implemented to investigates their effect on the mechanical properties of Brass 65-35 formed by single point incremental sheet metal forming process. To response this task, a fully digital integrated system from CAD modeling to finished part (CAD/CAM) for SPIF process has been developed in this paper. The photo-micrographs shows an identical grain formation due to the plastic deformation of the incremental forming process, change in the grain shape and size was observed. It’s found that the adaptive tool path play a significant role to increase the hardness of the formed specimen from (48 to 90 HV) and the grain texture of the formed specimen found as round shape, while the hardness is increased in little amount from (48 to 74 HV) in the specimen formed using helical and it’s grain texture was found as needle shape.